Does donor treatment with inotropes and/or vasopressors impact post‐transplant outcomes?. Issue 4 (28th January 2023) - Blitzer, David; Baran, David A.; Lirette, Seth; Copeland, Jack G.; Copeland, Hannah
Abstract: Purpose: The purpose was to evaluate the effects of the most commonly used cardiac donor inotropes/vasopressors on subsequent post‐heart transplant survival. Methods: Adult heart transplant recipients from January 2000 to June 2022 were identified in the United Network for Organ Sharing (UNOS) database. Exclusion criteria included: multiorgan transplants, donor age < 15, and recipient age < 18. Donors receiving vasoactive medications at the time of procurement were compared to donors not receiving these medications. Those on vasoactive medications were stratified by medication: phenylephrine, dopamine, dobutamine, norepinephrine and epinephrine, the combination of these agents, and the concomitant administration of vasopressin with any single agent alone or in combination. The primary area of interest was short‐and‐long‐term survival. Survival at 30 days, 1 year, and long‐term (Median = 13.6 years) was compared using logistic and Cox models to quantify survival endpoints. Results: A total of 45, 198 donors met inclusion criteria and had data on the use of vasoactive agents available. Mean donor age was 32.3 years with 71% male. Vasoactive medications and potential combinations included phenylephrine in 8156 donors (18.0%), dopamine in 9550 (21.1%), dobutamine in 718 (1.6%), epinephrine in 332 (.73%), and norepinephrine in 4854 (10.7%). A total of 25, 856 donors (57.2%) were receiving vasopressin at the time of procurement. There was no impact of donor inotropes on 30‐day survival. Donors receiving one inotrope and no vasopressin were associated with increased 1 year mortality (OR 1.14; p = .021), as were donors receiving 2+ inotropes and no vasopressin (OR 1.26; p = .006). For individual agents, 1 year mortality was increased for dopamine (OR 1.11; p = .042) and epinephrine (OR 1.59; p = .004). Conclusions: There is no difference in heart transplant recipient survival at 30 days when the donor is receiving inotropes without vasopressin at the time of procurement. Inotropic support without vasopressin is associated with greater 1 year mortality. The impact of donor inotropic support on long term heart transplant survival, and the interaction with vasopressin warrants further study.